2016
DOI: 10.12688/f1000research.9509.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting stone free rate of primary percutaneous nephrolithotomy on staghorn calculi: a single center experience of 15 years

Abstract: Objectives: Percutaneous nephrolithotomy on staghorn calculi is challenging for urologists because it is difficult to remove all of the stones. The purpose of this study was to evaluate the associated factors of stone-free rate after primary percutaneous nephrolithotomy on staghorn calculi in a large series of patients at a single, tertiary referral, endourologic stone center. Methods: We collected data from medical record between January 2000 and December 2015. A total of 345 primary percutaneous nephrolithot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…F1000Research: Dataset 1. Raw data for Table 1 , Table 2 , and Table 3 of 'Factors affecting stone free rate of primary percutaneous nephrolithotomy on staghorn calculi: a single center experience of 15 years’, 10.5256/f1000research.9509.d134117 42 …”
Section: Data Availabilitymentioning
confidence: 99%
“…F1000Research: Dataset 1. Raw data for Table 1 , Table 2 , and Table 3 of 'Factors affecting stone free rate of primary percutaneous nephrolithotomy on staghorn calculi: a single center experience of 15 years’, 10.5256/f1000research.9509.d134117 42 …”
Section: Data Availabilitymentioning
confidence: 99%
“…Other similar studies also reported similar results, where SFR after standard PCNL seemed to be lower in patients with a higher BMI. 32,33 However, the effect of BMI on PCNL outcomes remains debatable, as several studies by Ferreira et al, 34 Alyami et al, 35 and Akbulut et al 36 showed that PCNL outcomes were independent of BMI. Thus, a large population-based study or randomized controlled trial is needed to ascertain the effect of BMI on PCNL outcomes, especially in the more recent mini-PCNL group.…”
Section: Discussionmentioning
confidence: 99%
“…It is of note that conversely to these observations, the European Association of Urology guidelines on urolithiasis discusses that treatment success of PCNL is hardly affected by stone size [18]. However, the evidence for stone size as an important predictor for treatment success rises [21,22]. Additionally, the reported stone-free rates after PCNL were remarkably lower when treating exclusively large kidney stones than stone size-independent studies (49-78 vs. 71-100%) [1,23].…”
Section: Discussionmentioning
confidence: 99%